2021
DOI: 10.5935/1518-0557.20210108
|View full text |Cite
|
Sign up to set email alerts
|

The most important medicinal plants affecting sperm and testosterone production: a systematic review

Abstract: Objective: Infertility, defined as the inability to conceive after one year of intercourse without the use of contraception, affects 15% of couples. Many factors, such as genitourinary tract infections, endocrine disorders, immunological factors and drug-related injuries, affect the male reproductive system and cause infertility. Due to men's fear of infertility, it is very important to pay attention to medicinal plants that are effective in male fertility. Therefore, the aim of this study was to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…All studies (except one) have demonstrated the beneficial effects of these medicinal plants on male reproduction; however, more clinical trials are required to establish the maximum dose and treatment duration with herbal medicines, as well as to evaluate any possible adverse effects of this therapy, in order to develop novel strategies for the treatment of male infertility (Roozbeh et al 2021). The authors of the new systematic review of 2022 searched the databases Science Direct, PubMed, Scopus, PubMed Central, and Scientific between 2000 and 2020 using search queries (Boroujeni et al 2022). Based on the results of 35 studies, it was determined that such plants as Apium graveolens, Cinnamomum camphora, Cornus mas, Satureja khuzestanica, Withania somnifera, Fumaria parviflora, Zingiber officinale, Cinnamomum zeylanicum and Phoenix dactylifera had a positive effect on reproduction, and demonstrated antioxidant effects and a low frequency of side effects (Boroujeni et al 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies (except one) have demonstrated the beneficial effects of these medicinal plants on male reproduction; however, more clinical trials are required to establish the maximum dose and treatment duration with herbal medicines, as well as to evaluate any possible adverse effects of this therapy, in order to develop novel strategies for the treatment of male infertility (Roozbeh et al 2021). The authors of the new systematic review of 2022 searched the databases Science Direct, PubMed, Scopus, PubMed Central, and Scientific between 2000 and 2020 using search queries (Boroujeni et al 2022). Based on the results of 35 studies, it was determined that such plants as Apium graveolens, Cinnamomum camphora, Cornus mas, Satureja khuzestanica, Withania somnifera, Fumaria parviflora, Zingiber officinale, Cinnamomum zeylanicum and Phoenix dactylifera had a positive effect on reproduction, and demonstrated antioxidant effects and a low frequency of side effects (Boroujeni et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The authors of the new systematic review of 2022 searched the databases Science Direct, PubMed, Scopus, PubMed Central, and Scientific between 2000 and 2020 using search queries (Boroujeni et al 2022). Based on the results of 35 studies, it was determined that such plants as Apium graveolens, Cinnamomum camphora, Cornus mas, Satureja khuzestanica, Withania somnifera, Fumaria parviflora, Zingiber officinale, Cinnamomum zeylanicum and Phoenix dactylifera had a positive effect on reproduction, and demonstrated antioxidant effects and a low frequency of side effects (Boroujeni et al 2022). Many nutraceuticals can stimulate steroidogenesis in men, according to Santos et al (2022).…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned earlier, acting on the HPG axis and thus affecting sex hormone balance appears to be an essential modulation. A plausible mechanism may be that Ashwagandha acts on GABA receptors in the hypothalamus, facilitating the expression of GnRH [49], which in turn stimulates the pituitary gland to secrete LH and FSH [50,51].…”
Section: Ashwagandha's Impact On the Reproductive Systemmentioning
confidence: 99%
“…Recently, use of traditional medicines from medicinal plants has increased in treating male infertility. Many studies show evidence of the effect of medicinal herbs on the testicular tissue, epididymis, spermatogenesis, steroidogenesis, testosterone production, erection function, ejaculation, and libido [ 26 , 27 ]. Therefore, the aim of this study was to investigate the effect of Curculigo orchioides extract on testicular histopathology alteration and blood testosterone levels in heat stress-induced male mice.…”
Section: Introductionmentioning
confidence: 99%